A Sharper Global Error Bound for the Generalized Nonlinear Complementarity Problem over a Polyhedral Cone - Hongchun Sun; Yiju Wang (Abstract and Applied Analysis)
We revisit the global error bound for the generalized nonlinear complementarity problem over a polyhedral cone (GNCP). By establishing a new equivalent formulation of the GNCP, we establish a sharper global error bound for the GNCP under weaker conditions, which improves the existing error bound estimation for the problem.